Antibacterial efficacy of muringa seed extract and potato peel extract Against Enterococcus faecalis - M C Noushad; K Ashraf; M P Suneetha (Wolters Kluwer Medknow Publications, 2020)
Background: Elimination of infection and prevention of reinfection should be the main goal in the treatment of apical periodontitis. The most challenging part of endodontics is the complete disinfection of root canal system. Herbal alternatives have emerged as the more biofriendly approach in root canal irrigation and disinfection. Aim and Objective: The aim of this study was to evaluate the antimicrobial efficacy of natural extracts like muringa seed and potato peel extract against Enterococcus faecalis. Materials and Methods: The antimicrobial activity was determined using agar diffusion test. The solutions were divided into three groups: Group I- Muringa seed extract, Group II- potato peel extract, and Group III-5.25% sodium hypochlorite. The zones of inhibition of growth were recorded. The strain used for this study was Enterococcus faecalis ATCC 29212. Results and Conclusion: Muringa seed extract (Group I) demonstrated the best result among the tested solutions. Although there was no significant difference between potato peel extract (Group II) and 5.25% sodium hypochlorite (Group III). Within the limitations of this study, herbal extracts tested has shown significant antimicrobial action against Enterococcus faecalis.